The conditions of production in Superinteressante magazine's discourse on climate change (1995 - 2015) - Rangel Winch, Rafael (2017)
Journalistic discourse always is result of specific conditions of production that anchor the sayings about events, themes, problems and diverse individuals. In this research, we reflect especially on conditions of production that allow the reiteration of meanings about climate change in Superinteressante magazine. In our interpretive action, we mapped sayings about the climate issues constructed by the publication between 1995 and 2015. Based on the theoretical-methodological contributions of Discourse Analysis (AD), we located four Discursive Formations (DF) and ten Paraphrases Networks (PN) about climate change. The discussion of such categories points out how this magazine works, in its own discourse, the different dimensions of climate change.